B55 The effect of paravertebral anaesthesia on quality of life scores in breast cancer patients. (11th August 2022) - Chhabra, A; Seenu, V; Parshad, R; Dhar, A; Sharan, P; Pandey, RM; Mohanty, S; Mathur, S
Abstract : Background and Aims: Breast cancer is the commonest cancer worldwide.(1) Multiple level paravertebral anaesthesia (PVA) provides excellent analgesia with minimal PONV (2); therefore, we wanted to ascertain if PVA would improve quality of life (QoL) at 2weeks postoperatively in these patients. Methods: We included female patients of > 18 years, of ASA I-III, scheduled to undergo breast cancer surgery after ethics committee approval. Three validated QoL questionnaires for cancer patients were administered preoperatively and 2 weeks postoperatively i.e. the European Organisation for Research and Treatment of Cancer - QLQ-C30 (primary outcome), BR-23, the FACT-B and WHOQOL-bref questionnaires. (3–5) PVA group patients received USG, in-plane, PVA at T1-T6 levels together with Pecs-2 block and propofol sedation whereas the GA group received standard GA. Results: 65 patients were randomised: 34 in the PVA and 31 in GA group. Demographics were comparable except for younger age of PVA patients. At 24 hours lower pain scores (movement), lesser fentanyl consumption was observed in PVA patients [365 mcg (215, 595)] versus GA group [820 mcg (565, 1035)], P= 0.0001. QLQ-C30 scores at 2 weeks post-surgery (global health-QoL, physical, role, cognitive, social functioning) were significantly better in PVA as compared to GA patients after age and baseline score adjustment. Intra-group analysis revealed significant fall in body image, sexual functioning, breast, arm symptoms (QLQ-BR23 scores) and lower emotional, functional scores (FACT-B, WHOQOL-bref) in the GA group. Conclusions: Therefore, emotional, physical and functional quality of life was better maintained in PVA patients as compared to GA patients at 2 weeks post-surgery.